ANALISIS DETERMINAN PERDAGANGAN RUMPUT LAUT INDONESIA - Saragih AK; Burhanuddin Burhanuddin; Herawati Herawati (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2022)
Seaweed is a cultivated fishery commodity that has contributed to Indonesia’s national economy. Indonesia contributes 40% of the world's seaweed export volume. Export volume has increased, meanwhile, the domestic market has difficulty in obtaining raw materials. The aim of this research is to analyze the factors affecting the trade of Indonesian seaweed to seven destination countries (China, South Korea, France, Chile, Philippines, USA, and Japan). The analytical method used in this research is panel data with the Gravity Model approach with periods covering 2000 until 2019. The dependent variable is trading volume. The result of estimated factors affecting trade is real GDP per capita of Indonesia, real GDP per capita of destination countries, exchange rates, and economic distance, which significantly influence trading volume. Improvement of supporting facilities, protection for domestic industry to obtain quality raw materials, and improvement of technology to improve the quality of seaweed.